Pancreatic polypeptide and its central Y4 receptors are essential for cued fear extinction and permanent suppression of fear. (19th May 2016) - Verma, D; Hörmer, B; Bellmann‐Sickert, K; Thieme, V; Beck‐Sickinger, A G; Herzog, H; Sperk, G; Tasan, R O
Abstract : Background and purpose: Avoiding danger and finding food are closely related behaviours that are essential for surviving in a natural environment. Growing evidence supports an important role of gut‐brain peptides in modulating energy homeostasis and emotional‐affective behaviour. For instance, postprandial release of pancreatic polypeptide (PP) reduced food intake and altered stress‐induced motor activity and anxiety by activating central Y4 receptors. Experimental approach: We characterized [K 30 (PEG2)]hPP2‐36 as long‐acting Y4 receptor agonist and injected it peripherally into wildtype and Y4 receptor knockout (Y4KO) C57Bl/6NCrl mice to investigate the role of Y4 receptors in fear conditioning. Extinction and relapse after extinction was measured by spontaneous recovery and renewal. Key results: The Y4KO mice showed impaired cued and context fear extinction without affecting acquisition, consolidation or recall of fear. Correspondingly, peripheral injection of [K 30 (PEG2)]hPP2‐36 facilitated extinction learning upon fasting, an effect that was long‐lasting and generalized. Furthermore, peripherally applied [K 30 (PEG2)]hPP2‐36 before extinction inhibited the activation of orexin‐expressing neurons in the lateral hypothalamus in WT, but not in Y4KO mice. Conclusions and implications: Our findings suggests suppression of excessive arousal as a possible mechanism for the extinction‐promoting effect of central Y4 receptors and provide strong evidence that fear extinction requires integration of vegetative stimuli with cortical and subcortical information, a process crucially depending on Y4 receptors. Importantly, in the lateral hypothalamus two peptide systems, PP and orexin, interact to generate an emotional response adapted to the current homeostatic state. Detailed investigations of feeding‐relevant genes may thus deliver multiple intervention points for treating anxiety‐related disorders.